Santo Domingo, Alma Mater of San Marcos and La Casona, Identity, Heritage and Tourism in Lima - Castillo Yui, Nieves Cecilia (2019)
The cloisters of Santo Domingo were the first testimony of the existence of the Universidad Nacional Mayor de San Marcos, without a doubt a religious architectural and artistic jewel of the city of Lima valued for its real material heritage. La Casona is also a valuable testament to the viceroyal, emancipatory and republican life of Peru, therefore, it is important to recognize in both their valuable contribution to Peruvian culture and national identity for the cultural heritage they hold. Currently, tourism joins the two, as a result of this cultural historical link through knowledge and dissemination in tourism activity.